Kemampuan Literasi Matematika Siswa Berdasarkan Gaya Belajar - Nadila, Shinta Alfiatu; Lestiana, Herani Tri (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2024)
The results of the OECD-PISA state that the mathematical literacy skills of students in Indonesia are still relatively low. The objectives of this study are: 1) To analyze students' mathematical literacy skills in solving Two-Variable Linear Equation System (SPLDV) problems in terms of student learning styles; 2) To find out the factors causing the less than optimal mathematical literacy skills. The method used in this study is descriptive qualitative. The study subjects were 23 students in grade VIII at SMPN 1 Beber with 9 students interviewed, namely 3 students with a visual learning style, 3 students with an auditory learning style, and 3 students with a kinesthetic learning style. Assessment of mathematical literacy skills is based on 3 indicators of mathematical literacy skills: formulate, employ, and interpret. The results of this study indicate that: 1) In solving SPLDV problems, the mathematical literacy skills of students with an auditory learning style are better than those with other learning styles; 2) The factors causing the less than optimal mathematical literacy skills are personal factors and instructional factors.